Language use and attitudes of the bidayuh teenagers in Kota Samarahan-Kuching division, Sarawak = Penggunaan bahasa dan sikap remaja bidayuh di Bahagian Kota Samarahan-Kuching, Sarawak - Marienfelde, Jebi (Universiti Malaysia Sarawak, UNIMAS, 2009)
The study looks at the phenomenon of language shift among the Bidayuh teenagers in Kota Samarahan-Kuching division. The study aimed at investigating the language use of the Bidayuh teenagers in three domains, specifically home, school and friendship and their attitudes towards their own ethnic language. The objectives are: (1) to find out the Bidayuh teenagers first and second language, (2) to investigate the Bidayuh teenagers language proficiency in their ethnic language versus other languages, (3) to identify the Bidayuh teenagers patterns of language use in three domains; home, school, and friendship, and (4) to find out the attitude of the Bidayuh teenagers towards their ethnic language in order to determine the possibilities of language shift. The parti cipants involved in this study were 210 secondary schools students, who are Bidayuh aged between 13 to 17 years old. A survey research design was carried out using questionnaire as the instruments. The findings revealed that the language that the Bidayuh t eenagers use in all three domains is the ethnic language itself including Bahasa Melayu, which shows the tendency of language shift in the ethnic language. The findings also revealed that majority of the Bidayuh teenagers are in favour towards their ethnic language. Besides that, the phenomenon of language shift was found slower within the target Bidayuh teenagers due to the geographical area that is rural- area, which means there is a potential for language maintenance for the ethnic language.